Disaster Mitigation Based on Local Wisdom in the Muria Mountains - Khasan, Mohammad; Widjanarko, Mochamad; Wismar’ein, Dian; Prasetyo, Eko Budi (Universitas Pendidikan Ganesha, 2025)
This research aims to identify disaster mitigation behaviour in the community of Tempur Village, Jepara Regency, based on local wisdom. This research is qualitative research with a phenomenological approach with Mitebenkealhutanmuria instruments used through observation and interviews. Research informants in the study used the snowball technique. Five informants were obtained. The data analysis used was coding. Meanwhile, credibility is done by triangulating data and cross-checking informants. The results of the research findings are that Tempur Village is a disaster-prone area. Gaining knowledge and understanding of the consequences of disasters on the community enhances confidence and the ability to take measures to mitigate the impact of disasters by using local wisdom. The spiritual power that is generated collectively through customs and ethics such as the commemoration of the first night of Suro, Sedekah Bumi and Selametan Perempatan is believed by the community to be an effort to ward off “Balak” (disaster) and has the power to anticipate disasters, as well as provide safety for Tempur Village. Research implications theoretically need to be carried out to understand how local wisdom can be combined with modern mitigation strategies to be more effective and become a social psychology model of disaster mitigation that needs to consider the role of collective beliefs, social norms, and community identity in determining responses to disaster risk. Practically, local governments need to recognize and accommodate local wisdom practices in disaster mitigation policies. Traditional rituals and culture-based early warning systems can be part of broader mitigation strategies.